A Taxonomy to Understand Scaling of Innovation by African Enterprises - Armstrong, Chris; De Beer, Jeremy (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2021)
Grounded in empirical research findings and key statements in the literature, this article proposes a four-part taxonomy for mapping African knowledge-based enterprises’ efforts to achieve scale. The taxonomy, adapted from the framework proposed by Uvin et al. (2000), is comprised of scaling by expanding coverage; by broadening activities; by changing behaviour; and by building sustainability. The article sets out the framework and provides examples of the four scaling dimensions from empirical research conducted in Egypt, Tunisia, Morocco, Ghana, Nigeria, Ethiopia, Uganda, Kenya, Botswana, and South Africa.
Keywords: scaling, innovation, enterprises, Africa, definitions, taxonomies, scaling up, scaling out, scaling down, scaling in, expanding coverage, broadening activities, behaviour change, sustainability